Manajemen pendidikan dasar dan menengah - hidayat, sahrul haj (Maliki Interdisciplinary Journal, 2025)
Education aims to actualize students’ potential through learning methods and educational management that involve all parties. The approach used in this study is the theoretical approach method. Researchers can assess and study the journal’s contribution to current theoretical knowledge by using a theoretical framework. The conclusion obtained in this study is that Law Number 20 of 2003 concerning the National Education System regulates basic education in Indonesia, which is mandatory for nine years. The goal is to help students acquire basic mindsets, talents, and competencies to live in society. General and vocational secondary education is present after elementary school to improve intelligence, knowledge, personality, noble morals, and the ability to live independently and pursue higher education. Educational management includes planning, organizing, supervision, and development. School leadership aims to foster a culture of brotherhood and cooperation, while the Management Information System is also important for the efficiency and effectiveness of education in Indonesia.